Athletes' feeling states related to best and worst soccer games and the coaches' ability to recognize them - Kibirkstis, Ieva (2014)
The coach-athlete relationship is an important factor linked to the performance and well-being of athletes. Athlete’s feeling states prior to performance and the ability of a coach to monitor these states are equally important. However, this area still lacks the study of the coach’s ability to effectively “read” their players in their successful and unsuccessful performances. The purpose of this study was to examine the feeling states of eleven selected starters from a female Finnish 1st division football team prior to their best and worst games. A secondary aim was to assess the ability of the coaches to recognize their athletes’ feeling states prior to their successful and unsuccessful games. A mixed methods approach was taken. First, emotional and other performance related states were assessed using the Psychobiosocial state scale (PBS-S) and the Emotional State Profile (ESP-40). Individual profiles were developed for each athlete and then compared at an intra- individual and inter-individual level, as well as according to playing position. Then, these profiles, along with the list of the names of the 11 starters, were given to the coaches for a matching exercise in order to test their ability to accurately recognize the feeling states of their players. As expected, with regards to the feeling states prior to best games, the PBS profiles showed higher scores for the functionally helpful modalities, and lower scores for the dysfunctional ones. The ESP-40 showed a moderate IZOF-iceberg pattern for the best games, which is characterized by high optimal scores and low dysfunctional scores. Interestingly, these profiles showed high positive (optimal and dysfunctional) scores and low negative (optimal and dysfunctional) scores, instead of the original assumption of high optimal and low dysfunctional scores. However, the profiles associated to worst games did not fit our expectations, as the profiles were flat, instead of demonstrating the inverse- iceberg shape that was expected. Finally, the coaches struggled to match the emotional profiles to the names of the players. This finding is in line with previous research that showed that coaches are inaccurate in recognizing their athlete’s emotions, particularly in larger groups (Hanson & Gould, 1988). Further research in team sports and the coach- athlete relationship is required.